PERAN GURU AL-ISLAM DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL SISWA SMA MUHAMMADIYAH 6 PONDOK PESANTREN KARANGASEM PACIRAN LAMONGAN - Nashrudin Abdul Khair (STAI Muhammadiyah Paciran Lamongan, 2021)
This study aims to determine what the role of Al-Islam teachers in developing Emotional Intelligence students in SMA Muhammadiyah 6 Pondok Pesantren Karangasem Paciran Lamongan. The results of this study is expected to help educators to be more wise and know its role in developing students' emotional intelligence. The role of Al-Islam teachers in developing students 'emotional intelligence is that teachers should be able to deliver lessons according to shari'ah, always motivate students, maintain morals and obey rules, cultivate students' sense of concern for the people around them by doing activities such as visit the sick friends, the teacher is able to make the learning atmosphere becomes more fun and easy to understand so that students are motivated to the spirit of learning, the teacher is able to make the students have the ability to understand the surrounding environment in order to be able to interact and socialize and students can control their emotions well. This research is a qualitative research, data collection is done by using the method of observation, interview (interview) and documentation. Data analysis is done by giving meaning to the data collected and from that meaning can be drawn conclusion. Results from the study show. A. Urgency to develop emotional intelligence for the advancement of student education in SMA Muhammadiyah 6 Karangasem Paciran lamongan, which is self-motivation in learning, can relate well with others, and can know the emotions in yourself. B. The role of Al-Islam teachers in developing students' emotional intelligence in SMA Muhammadiyah 6 Karangasem Paciran Lamongan. 1. Convey the teachings in accordance with the Shari'ah, 2. Providing motivation to students, 3. Advising on keeping the morals and obedient to the rules. C. The method applied by Al-Islam teachers in developing students' emotional intelligence in SMA Muhammadiyah 6 Karangasem Paciran Lamongan. 1. Method of Approach, 2. Method of Recitation, 3. Method of class discussion, 4. Method Lecture and question and answer.